Trickling Filter with River Stone and Hose Piece Media Variations for Treating Poultry Slaughterhouse Wastewater - Alfiah, Taty; Naa, Aholiab Alfansen (Faculty of Civil Engeneering and Planning - ITATS, 2025)
The Poultry Slaughterhouse (RPU) operations menghasilkan wastewater dengan characteristics high organic matter dinyatakan dalam parameter (Biological Oxygen Demand) , (Chemical Oxygen Demand), suspended matter (Total Suspended Solid), and oils and fats sehingga harus diolah agar memenuhi effluent standard serta tidak mencemari perairan. Riset ini bertujuan untuk mengetahui apakah tickling filter dapat digunakan untuk mengolah poutry slaughterhouse wastewater. Wastewater taken form Wonokromo poutry slaughterhouse Surabaya. Penelitian dilaksankana menggunakan two wastewater tank, which (P1) untuk menampung slaughter wastewater, second tank (P2) to maintain waterpressure and tank pembagi ke two trickling filter reaktor. Trickling filter dalam penelitian ini menggunakan variasi media, first Trickling filter (R1) with stone media and second trickling filter (R2) with hose pieces media with flow rate 10 mililiter/menit. Trickling filter effluent be collected and examine at durataion 24, 96, 18 hours running and diukur nilai TSS, BOD and oils and fats remaining. Poutry Slaugherhouse wastewater distributed over trickling filter sehingga wastetwter tricle down to surface trickling filter media media. Concusion this research tat